Potential of Chitosan From Local Crab (Portunus Pelagicus) to Enhance Storability of Musa Paradisiaca L. - Buanasari, Buanasari; Sugiyo, Warlan; Fitriani, Nur; Suryaningsih, Suryaningsih (Jurnal Bahan Alam Terbarukan, 2019)
Potential waste of local crab carapace (Portunus pelagicus) as a source of chitosan as an active layer that can protect bananas has been studied. The process in this study consists of three stages. The first stage was the isolation of chitin through deproteinization process using 2.0 N NaOH solution with a ratio of 1:6 w/v and demineralization process using 1.5 N HCl solution with a ratio of 1:12 w/v. The second stage is the deacetylation stage using 50% NaOH solution with a ratio of 1:20 w/v. Fourier Transform Infra-Red (FTIR) Spectroscopy is used to determine the degree of deacetylation. The third stage is the banana coating application using chitin solution to determine the shelf life of bananas with variations in levels of 2, 2.5, 3 and 3,5 % w/v by immersion method for one hour. It was found that carapace crab, a part that was underutilized from crab, gave rise to chitin deacetylation with a deacetylation rate of 62.11%; pH 8.9 and water content of 7.677%. Chitosan-based coatings are applied to fresh bananas and are found to increase fruit firmness, and inhibit browning. The results show that chitosan-coated bananas have a longer storage time. The application of chitin deacetylated (chitosan) as fruit banana coater found that higher coater levels extend the shelf life of bananas with the best coater content is 3% b/v. It results in a shelf life of bananas for up to 12 days, this is longer than bananas without chitosan layer which only has a shelf life of four days. Increased coating rates have a positive effect on the shelf life of bananas. This study shows that waste from carapace crabs can be used to form active layers that can preserve fruit.